Toxicity Study and Anticonvulsant Effect of Ethanol Leaf Extract of Piliostigma thonningii Milne-Redhead (Fabaceae) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Piliostigma thonningii (Schumach) Milne-Redhead [Fabaceae] is a plant widely used locally for the treatment and management of several ailments which include epilepsy in Northeastern Nigeria.Objectives: This study aimed at evaluation of the toxicity and anticonvulsant effect of ethanol leaf extract of Piliostigma thonningii in rats and mice with a view to determining the efficacy of the plant as an anticonvulsant drug.Methods: Fresh leaves of Piliostigma thonningii were air-dried, pulverized and extracted using soxhlet extraction apparatus. Acute toxicity study was carried out by Lorke’s method and the anticonvulsant activity of the ethanol leaf extract was carried using pentylenetetrazole and strychnine-induced convulsion model on Wistar strain albino rats and mice respectively.Result: The soxhlet extraction yielded 21.04% w/w of extract after being concentrated. The oral and intraperitoneal LD50 were ≥ 5000 mg/kg implying that the extract is relatively safe according to literatures. Anticonvulsant effect of the ethanol leaf extract using pentylenetetrazole (PTZ), revealed the ability of the extract to confer protection on rats treated with doses of 200, 400 and 600 mg/Kg bd. wt. by exerting 60%, 80% and 80% protection on rat against PTZ induced convulsion respectively in a dose dependent manner as well as protected 20%, 60% and 80% of mice against death induced by strychnine when treated with 100, 200 and 400 mg/kg of ethanol extract. Conclusion: The ethanol leaf extract of Piliostigma thonningii was able to provide anticonvulsant effect and is relatively safe for consumption as medicine